Quand les acteurs locaux mobilisent le droit pour s’opposer aux grands projets : l’exemple de l’aménagement de la vallée du Bou Regreg (Rabat-Salé) - Hicham Mouloudi (Les Cahiers d’EMAM)
For efficiency, the Moroccan legislator intended for the particular case of the development of the BouRegreg valley, a series of exceptions to laws on urban planning and expropriation to allow the contracting authority to achieve its goals more easily. These exceptions are at the origin of an unequal power relationship between the developer and local stakeholders. If government departments and the municipality of Rabat have systematically endorsed the decisions of the contracting authority, the elected officials of the municipality of Salé and representatives of the inhabitants were strongly mobilized by deploying resources and novel repertoires of action in order to express their discontent against this fact. It is the law that allows local actors to oppose this development project, although it is always presented by the project owner as a project “Royal” during the public consultation phase (Survey public) and approval of agreements by local elected officials. The project owner has conducted an “integrative” negotiation with the local residents mobilized. Obviously, these mobilizations were favorable to arrangements and compromises with the project owner who ultimately decided not only to suspend the evictions but also to improve the living environment of the residents.